2013
DOI: 10.1590/s1516-89132013000300007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of melatonin and/or complex vitamin B1,B6,B12 in modulating epinephrine-induced stress in male rats

Abstract: This study was undertaken to determine the modulating effects of intramuscular administration of melatonin (MT)(1mg / kg) and/or Tri-B (B 1 , B 6 and B 12 ) (20mg/kg) on body weight and some biochemical changes in rats induced by Epinephrine (Epi) injection. The data showed that MT and/or Tri-B treatment effectively improved the changes in malondialdehyde, lipid profile, blood sugar level and insulin. MT and/or Tri-B administration following Epi improved partially the decrease in body weight and liver glycogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Another study showed that melatonin blunt the natural sympathetic arising of the first morning orthostatism and reduced the pressor effects of norepinephrine in pharmacological conditions . Yossef EL‐Toweissy et al study showed that the administration of melatonin and complex of vitamin B 1 , B 6 , B 12 following epinephrine injection partially improved the decreased body weight and liver glycogen levels.…”
Section: Interactions Between Melatonin and Catecholamines Regulationmentioning
confidence: 99%
“…Another study showed that melatonin blunt the natural sympathetic arising of the first morning orthostatism and reduced the pressor effects of norepinephrine in pharmacological conditions . Yossef EL‐Toweissy et al study showed that the administration of melatonin and complex of vitamin B 1 , B 6 , B 12 following epinephrine injection partially improved the decreased body weight and liver glycogen levels.…”
Section: Interactions Between Melatonin and Catecholamines Regulationmentioning
confidence: 99%